Quality control to reduce production defects using control chart, fishbone diagram, and FMEA - Yudha Adi Kusuma; Halwa Annisa Khoiri; I Made Aryantha A.; Bagus Herlambang (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Quality improvement is necessary to overcome the occurrence of defective products during the production cycle. The occurrence of defective products is difficult to avoid. Therefore, the Sugar Factory (SG) business unit at PT XYZ began to implement quality control for sugar production. Based on these events, an analysis of quality measurement is carried out through this research. The methods used in this research are control chart, fishbone diagrams, and failure mode and effect analysis (FMEA). The results of the control map measurement using the p-chart and u-chart show that there is no sugar production process that is out of control. Although nothing is out of control, it is also necessary to analyze it using a fishbone diagram to determine the cause of the defects that occur. The results of the measurements with FMEA can be known sub-factors that have the highest RPN, namely negligence of operations, poor sugar cane sorting, changes in production schedules, incomplete repair areas, and poorly organized layouts. From the results of data processing, it can be seen that quality control needs to be carried out by the company. One of them is by making standard operating procedures (SOP) related to the sugar processing process. In addition, the raw materials for making sugar also need to be considered, so that the process will produce sugar with better quality